DETERMINANTS OF THE UTILIZATION OF OUTPATIENT AMONG CHILD IN INDONESIA - Lindia Herawati; Haerawati Idris (Faculty of Public Health, Sriwijaya University, 2019)
Background: Child's health becomes the government concern in developing countries. Improving child's health is a challenge for developing countries due to poor health care. Children tend to need more health services as they are more susceptible to various diseases. This study was aimed to determine the determinants influencing outpatient services utilization on children in Indonesia. Method: This research was a descriptive with cross-sectional design research using quantitative approach. The data were obtained from secondary data of the Indonesian Family Life Survey (IFLS) 2014. The dependent variable was the number of health service visits on children. In this study, the samples were 2,472 0-14 years old individuals selected according to inclusion and exclusion criteria. The data were analyzed using binomial negative regression. Result:The study found out that child using health services at least one outpatient visit in the last 4 weeks was 75.77%. Woman, perception of ill,parentalformalemployment, parental education (high), economic statuswere statistically related to utilization of health service for outpatient Conclusion:The perception of ill greatly affects the children in outpatient health service utilization, it is expected that government gives policy by family approach as theeffort of family member caring, health protection and improvement especially for child. Keywords:,, ,